Auto‐inflammation and auto‐immunity pathways are associated with emergence of BOS in pediatric lung transplantation. (10th February 2022) - Conrad, Carol K.; Hedlin, Haley; Chin, Hyunsook; Hayes, Don; Heeger, Peter S.; Faro, Albert; Goldfarb, Samuel; Melicoff‐Portillo, Ernestina; Thalachallour, Mohanakumar; Odim, Jonah; Schecter, Marc; Storch, Gregory A.; et al.
Abstract: Background: Long‐term survival after lung transplantation (LTx) is limited by chronic lung allograft dysfunction (CLAD). Methods: We report an analysis of cytokine profiles in bronchoalveolar lavage samples collected during a prospective multicenter non‐interventional trial primarily designed to determine the impact of community‐acquired respiratory viral infections (CARV) in outcomes after pediatric LTx. In this analysis, we identify potential biomarkers of auto‐inflammation and auto‐immunity associated with survival and risk of bronchiolitis obliterans (BOS) after LTx with cytokine analysis of bronchoalveolar lavage fluid (BALF) from 61 pediatric recipients. Results: Higher IL‐23 ( p  = .048) and IL‐31 ( p  = .035) levels were associated with the risk of BOS, and lower levels of epithelial growth factor (EGF) ( p  = .041) and eotaxin (EOX) ( p  = .017) were associated with BOS. Analysis using conditional inference trees to evaluate cytokines at each visit associated with survival identified soluble CD30 ( p  < .001), pro‐inflammatory cytokine IL‐23 ( p  = .02), and sTNFRI ( p  = .01) below cutoff levels as associated with BOS‐free survival. Conclusions: Our results indicate that post‐LTx survival in children may be linked to activation of alternate pathways of the immune system that affect airway remodeling in addition to activation of "classical" pathways that have been described in adult LTx recipients. These may indicate pathways to target for intervention.